RELATIONSHIPS BETWEEN REPORTED EARNINGS AND STOCK PRICES IN THE ELECTRIC UTILITY INDUSTRY. - O'Donnell, John L. (The Accounting Review, 1965)
Abstract Experts have long debated the theoretical problem of defining business income and the much greater difficulties of translating any definition into an operationally feasible system of accounts. That is to say, a set of accounts that will consistently and unambiguously reveal what has occurred to net worth during a series of selected time periods. As it is, the same data can be organized according to "generally accepted accounting principles" and be made to show radically different net profits available for stockholders. Many factors are contributing to the confusion, including a variety of acceptable methods for spreading period charges. For example, the ways in which inventory or fixed assets are handled can have a significant impact upon reported profits. These profits in their turn play a key role in influencing a wide range of important private and public policy decisions. In 1954 the government permitted firms to elect accelerated depreciation, for new fixed assets as an alternative to the straight-line method.